Abnormally Invasive Placenta Diagnosed On Ultrasonography Among High-Risk Women With Placenta Previa - Waheed, Fatima; Batool, Fatima; Raza, Asim (Journal of Rawalpindi Medical College, 2025)
Objective: The main aim of the study was to find the frequency of abnormally invasive placentas diagnosed on ultrasonography among high-risk women with placenta previa and to assess the association of all three types of placental invasion with placenta previa in prior pregnancies, advanced maternal age and multiple gestations Methods: This descriptive, cross-sectional study was conducted at CMH Medical College, Lahore, from September 2024 to January 2025 after the approval of the ethical review committee. The data analysis procedure was systematically executed using IBM SPSS 26.0. The Chi-square test was applied. Results: The study included 165 participants, aged 26-40 years, with 74.5% (n=123) experiencing vaginal bleeding and 95.8% reporting pelvic pain. Among the cases analysed, 93.9% (n=155) were diagnosed with placenta accreta, while placenta increta was observed in 4.2% (n=7), and placenta percreta in 1.8% (n=3). All participants had a history of previous uterine surgery (100%), and 50.3% (n=83) had a prior history of placenta previa. Regarding placenta previa grades, Grade 1 was the most common (67.9%, n=112), followed by Grade 2 (25.5%, n=42), Grade 3 (4.8%, n=8), and Grade 4 (1.8%, n=3). A positive history of placenta previa was found in 32.7% of Grade 1 cases, 13.3% of Grade 2, and 3.0% of Grade 3. Notably, a positive history of placenta previa was linked to higher rates of placenta accreta, especially in women aged ≥35 years (4.2%). Conclusion: Among high-risk women with placenta previa, abnormally invasive placenta (AIP) is a serious obstetric complication that poses significant feto-maternal risks. For the early and accurate diagnosis of AIP, Ultrasound is the modality of choice, as it is real-time, inexpensive and radiation-free, making timely interventions and improved perinatal outcomes. Keywords: Placenta Previa, Placenta Accreta, Placenta Percreta, Placenta Increta, Pregnancy, High-Risk.